Inhibitor designing, virtual screening, and docking studies for methyltransferase: A potential target against dengue virus - Jagbir Singh; Mahesh Kumar; Rani Mansuri; Ganesh Chandra Sahoo; Aakash Deep (Journal of Pharmacy and Bioallied Sciences, 2016)
Aim: Aim of this work was to design and identify some S-adenosyl-L-homocysteine (SAH) analogs as inhibitors of S-adenosyl-L-methionine-dependent methyltransferase (MTase) protein using computational approaches. Introduction: According to the current scenario the dengue has been a global burden. The people are being killed by dengue virus in an abundant number. Despite of lot of research being going on dengue worldwide, there is no single drug which can kill its virus. This creates an urge for new drug target identification and designing. MTase has been reported as an effective target against dengue virus as it catalyzes an essential step in methylation and capping of viral RNA for viral replication. Materials and Methods: The crystal structure of MTase in complex with SAH was used for designing new analogs of SAH. SAH analogs designed were analyzed on the basis of docking, ADMET, and toxicity analysis done using Discovery Studio 3.5. Results: Seventeen analogs found noncarcinogenic, nonmutagenic, as well as good ADMET properties and good drug-like profile. Conclusion: These SAH analogs, inhibitors of MTase may act as drugs against dengue virus. Further synthesis and biological testing against dengue virus is under observation.